2010
DOI: 10.1002/acr.20235
|View full text |Cite
|
Sign up to set email alerts
|

Utility‐based outcomes made easy: The number needed per quality‐adjusted life year gained. An observational cohort study of tumor necrosis factor blockade in inflammatory arthritis from Southern Sweden

Abstract: Objective. To introduce a novel, simple, utility-based outcome measure, the number needed per quality-adjusted life year (QALY) gained (NNQ), and to apply it in clinical practice in anti-tumor necrosis factor (anti-TNF)-treated patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), and spondylarthritis (SpA). Methods. The NNQ is the number of patients one has to treat in order to gain 1 QALY. It is calculated as the inverted value of the utility gain (area under the curve) over 1 year in a cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Ten of the studies (6 medium sized and 4 small; 6,289 patients) were individual patient analyses of one or more randomized trials of long duration (over 8 weeks) or appropriate duration for the condition being treated; one more was a small trial of medium duration (4 weeks; 41 patients) . Two prospective cohort studies of long duration (1 small sized, 1 medium; 1,387 patients) also provided data . Study duration is regarded as an important marker of clinical trial validity, as is not using inappropriate imputation methods .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten of the studies (6 medium sized and 4 small; 6,289 patients) were individual patient analyses of one or more randomized trials of long duration (over 8 weeks) or appropriate duration for the condition being treated; one more was a small trial of medium duration (4 weeks; 41 patients) . Two prospective cohort studies of long duration (1 small sized, 1 medium; 1,387 patients) also provided data . Study duration is regarded as an important marker of clinical trial validity, as is not using inappropriate imputation methods .…”
Section: Resultsmentioning
confidence: 99%
“… activities of daily living or enjoyment of life global impression depression or mood fatigue sleep function ability to work (employment or domestic) quality of life using standard questionnaires …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the improvements reported is not trivial and is perhaps best explained using the quality‐adjusted life year (QALY), which has a scale from 1 (perfect health for 1 year) to 0 (death). Health status increases over 1 year were 0.22 with successful tumor necrosis factor (TNF) inhibitor in rheumatoid arthritis, 0.35 for ≥ 50% pain intensity reduction in painful diabetic neuropathy, and 0.11 for the same outcome in fibromyalgia . In tapentadol trials in osteoarthritis or chronic low back pain, patients tolerating treatment with tapentadol or oxycodone and completing the trial were likely those with good pain benefit with increments of 0.31 .…”
Section: Resultsmentioning
confidence: 99%
“…Observational data from population studies provide useful insights. In Sweden, Gulfe et al 50 reported changes in 1,001 RA patients treated with TNF inhibitors. They found that EuroQol scores improved by a mean of 0.21 (95% CI: 0.19, 0.22).…”
Section: Quality Of Lifementioning
confidence: 99%